LAW ENFORCEMENT AGAINST CHILDREN AS CRIMINAL PERPETRATORS THE BRAWL IN PERCUT SEI TUAN FROM THE PERSPECTIVE OF CRIMINAL LAW AND ISLAMIC CRIMINAL LAW - Rabiathul Adawiyah Nasution; Seva Maya Sari (Journal Analytica Islamica, 2025)
Juvenile delinquency, as an act of violating laws and social norms during the transitional stage of adolescence, has shown an alarming increase every year in Indonesia. One of the most serious and recurring forms of juvenile delinquency is student or gang brawls, which are mass fights often involving sharp weapons and have resulted in numerous casualties. This phenomenon is driven by various factors, both internal (identity and self-control) and external (environment, family, and education), with motives that are often unclear, driven by group solidarity and the pursuit of social recognition (testing strength and courage). Legally, brawling constitutes a criminal act under the Indonesian Penal Code (Articles 170, 351, 355, and 358), which carries imprisonment sanctions. For juvenile offenders (Children in Conflict with the Law/ABH), legal proceedings refer to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. Furthermore, Islamic Criminal Law strictly prohibits all forms of violence and acts that demean others. Although there are existing regulatory frameworks such as the Minister of Social Affairs Regulation No. 9 of 2015 on the social rehabilitation of juvenile offenders, field observations (Case Study at Percut Sei Tuan Police Station) show that handling brawl cases merely by advising and returning the children to their parents fails to create a deterrent effect, leading to a high rate of recidivism. This condition emphasizes that the existing solutions, including the roles of parents and schools, are no longer effective. Therefore, this study aims to thoroughly examine “The Enforcement of Sanctions Against Children as Perpetrators of Brawl Crimes in the Perspective of Criminal Law and Islamic Criminal Law”, focusing on a case study at Percut Sei Tuan, in order to evaluate the effectiveness of law enforcement and to identify better efforts in addressing this recurring juvenile crime..